Characterization of Allergic Manifestations in Dental Professionals - Oviedo-Quirós, Jorge; Madriz-Montero, Luis; Lorz-Ulloa, Patricia (Odovtos - International Journal of Dental Sciences, 2021)
The aim was to determine the prevalence and types of the allergies present among dental professionals in Costa Rica. We performed a cross-sectional study on 664 dentists who completed a self-reported questionnaire. A descriptive cross-sectional study with inferential analysis was carried out. Dentists reported allergies prior to studying dentistry in 39% of cases, 36% reported chronic illnesses, and 61% of the dentists reported first-degree relatives with some type of allergic reaction. Different allergies had a similar prevalence among the dental professionals (ranging between 19%-26%), all allergic manifestations occurred within the first 120 minutes after exposure. The average time of exposure to dentistry-related environments was 16 years (95% CI) among all the dentists surveyed. There is a positive correlation between the presence of a chronic illness and the predisposition to develop allergic reactions among dentists. In addition, there is a directly proportional relationship between age, time of exposure to dental environments, and the risk of developing allergic conditions to dental materials. The main adverse reactions reported due to exposure to dental materials, medicines and/or food were gastrointestinal, skin, and respiratory problems.